2007
DOI: 10.1002/jbm.a.31563
|View full text |Cite
|
Sign up to set email alerts
|

Effect of controlled release of fibroblast growth factor‐2 from chitosan/fucoidan micro complex‐hydrogel on in vitro and in vivo vascularization

Abstract: We produced a chitosan/fucoidan micro complex-hydrogel as a carrier for controlled release of heparin binding growth factors such as fibroblast growth factor (FGF)-2. Material consisting of a soluble chitosan (CH-LA) mixed with fucoidan yielded a water-insoluble and injectable hydrogel with filamentous particles. In this study, we examined the ability of the chitosan/fucoidan complex-hydrogel to immobilize FGF-2 and to protect its activity, as well as the controlled release of FGF-2 molecules. The chitosan/fuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
81
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(84 citation statements)
references
References 25 publications
2
81
0
Order By: Relevance
“…BMP can induce MSC differentiation into chondrocytes and osteoblasts 6,15) , and bFGF promotes the proliferation of differentiated MSCs 7,16,17) . At 4 w, 8 w, and 12 w after operation, new bone formation area in Group C was larger than that in Group B, which was larger than Group A, with significance (P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…BMP can induce MSC differentiation into chondrocytes and osteoblasts 6,15) , and bFGF promotes the proliferation of differentiated MSCs 7,16,17) . At 4 w, 8 w, and 12 w after operation, new bone formation area in Group C was larger than that in Group B, which was larger than Group A, with significance (P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…The bFGF is a powerful angiogenic growth factor 7,20) . In this study, anatomical observation showed that at 2 w and 4 w after operation, fresh tissues grew actively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All the statistical analyses were carried out with GraphPad Prism Version 5.0 software. The integration of growth factors (GFs) in controlled release systems is a useful and much-explored method to improve their efficacy in vivo [28][29][30][31][32]. However, it is assumed that inducing the repair of complex tissues, such as cartilage, might only be possible through the orchestrated co-delivery of two or more GFs.…”
Section: Discussionmentioning
confidence: 99%
“…The model aggregates were prepared using fucoidan (a sulfated polysaccharide found in brown seaweed) and chitosan (a partially deacetylated derivative of the amino polysaccharide, chitin) according to a gel preparation protocol originally developed by Nakamura et al (2008) for pharmaceutical purposes. Fucoidan was extracted from Kjellmanialla crassifolia (Gagomekombu) according to Nakamura et al (2008). Gagome-kombu powder (10 g) (Toyonaka Matumae Konbu Honpo Corp., Osaka, www.kobuya.net) was added to 100 ml 70% by volume ratio (v/v) ethanol containing 0.1 M acetic acid in a 200 ml conical glass flask.…”
Section: Preparation Of Model Aggregatesmentioning
confidence: 99%